Use of Glucagon-like peptide 2 (GLP-2) analogs in inflammatory bowel disease - Dobromiła Osuch; Piotr Zatyka; Adam Słomczyński; Agata Pawłowska; Michal Rabenda; Piotr Janik; Dominika Opala (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Inflammatory bowel disease (IBD) is a chronic condition that involves long-term treatment and chronic idiopathic inflammation within the gastrointestinal tract. The predominant forms of IBD are: Crohn's disease and ulcerative colitis. These diseases cause significant physical as well as psychological dysfunction - patients with this condition are thought to have an increased risk of depression as well as anxiety. Standard treatment for IBD most commonly includes aminosalicylates, corticosteroids, immunomodulatory drugs, and biologic therapy. In some cases, particularly when it comes to Crohn's disease, it is necessary to remove a portion of the inflamed bowel. Multiple segmental bowel resections can result in the rare but serious complication of short bowel syndrome, which leads to intestinal failure and necessitates parenteral nutrition. Glucagon-like peptide-2 exhibits intestinotropic properties and also acts as a growth factor in the gastrointestinal tract, thereby increasing intestinal perfusion, causing increased absorption of nutrients, and enhancing proliferative mechanisms while inhibiting apoptotic processes. Methods: We carefully reviewed the medical literature on inflammatory bowel disease, short bowel syndrome and the potential treatment of this condition with GLP-2 and its analogs. The materials for the analysis we presented came from the PubMed database. Conclusions: Glucagon-like peptide 2 (GLP-2) analogs may prove to be new treatments for short bowel syndrome (SBS). They exhibit growth-stimulating effects on the intestinal membrane and promote normal function.